XXIV Balcanicum, Greeks and Greece in the politics and culture of Southeast Europe, Poznań, October 24–25, 2025 - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2025)
The XXIV Balcanicum conference, entitled Greeks and Greece in the Politics and Culture of Southeast Europe, was held in Poznań on 24–25 October 2025. The event, organized by the Balkan Studies Commission in cooperation with the Faculty of History at Adam Mickiewicz University, gathered scholars from Poland and abroad who presented 23 papers on topics ranging from Byzantine heritage and early modern influences to modern Greek diplomacy and cultural identity. The conference highlighted the central role of Greece and Greek culture in shaping the political, intellectual, and social landscape of Southeast Europe.